2022
DOI: 10.26434/chemrxiv-2022-b8j51
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electrochemical Carbon Dioxide Capture and Concentration

Abstract: Electrochemical carbon capture and concentration (eCCC) offers a promising alternative to thermochemical processes as it circumvents the limitations of temperature-driven capture and release. This review will begin by discussing the history of eCCC, describing early work in the field and the motivation for pursuing such a process. We will then transition towards discussing more recent approaches, with a heavier emphasis on methods that employ redox mediators to facilitate CO2 capture and release. These methods… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 132 publications
0
7
0
Order By: Relevance
“…The raw frame data was processed using SAINT 2 and SADABS 3 to yield the reflection data file. Subsequent calculations were carried out by using the SHELXTL 4 program package. There were no systematic absences nor any diffraction symmetry other than the Friedel condition.…”
Section: Physical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The raw frame data was processed using SAINT 2 and SADABS 3 to yield the reflection data file. Subsequent calculations were carried out by using the SHELXTL 4 program package. There were no systematic absences nor any diffraction symmetry other than the Friedel condition.…”
Section: Physical Methodsmentioning
confidence: 99%
“…The release of CO 2 is achieved by heating the sorbent (383 K for monoethanolamine). 3,4 However, these thermal-swing methods can only achieve 5−40% of the maximum theoretical energy efficiency. 1,5 Electrochemical methods can achieve greater theoretical energy efficiencies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…K binding is calculated using eq 5, 27 which has been previously adopted to evaluate the CO 2 -binding strength. 17,28 = [ ] ( )…”
Section: •−mentioning
confidence: 99%
“…14,15 In contrast, electrochemical carbon capture, featuring isothermal operation and nonvolatile redox-active materials, offers a promising alternative. 10,16 Early studies demonstrated the use of quinone derivatives in electrochemical systems in organic solvents. 17−19 Later, aqueous systems, including the development of electrochemical-mediated amine regeneration (EMAR) developed by our laboratory in 2013, played a significant role in advancing this field.…”
Section: Introductionmentioning
confidence: 99%